Impact of GMO Products on Human Health - Fayzullaeva Munisakhan Akmalovna (Scholars Digest Publishing, 2023)
Genetically modified organisms (GMOs) have become increasingly prevalent in the global food system over the past few decades. However, the impact of GMO consumption on human health remains an ongoing scientific debate with valid arguments on both sides. This article aims to examine the current state of research on the relationship between GMO foods and health outcomes in humans. A review of studies investigating effects such as allergenicity, toxicity, nutritional effects, and gut microbiome implications is provided. Both animal studies and epidemiological data are considered. The analysis finds potential risks depend highly on the exact genetically engineered trait and requires careful case-by-case evaluations. Limited evidence also exists of possible benefits, such as reduced toxicity from certain GM crops. Overall, the health effects of GMOs are complex with more long-term research still needed, though no definitive harms have been proven so far according to a consensus of scientific organizations. Continued monitoring and open communication on new findings is important as this controversial field continues to evolve.
Keywords: GMOs, genetic engineering, human health, toxicity, allergenicity, nutritional effects, gut microbiome, epidemiology, animal studies, Golden Rice, Bt crops, herbicide tolerance, recombinant proteins, scientific consensus, regulatory guidelines.